Table of Content - - (Journal of Curriculum and Teaching Methodology, 2024)
Table of Content: 1. Beliefs of Arabic language teachers towards employing active learning in first-year basic education schools in Sultanate of Oman Dr. Humaid Muslem Alsaidi, Mr. Arif Rabiaa Alyazidi 2. Analysis of book 4 in light of the requirements of the science, technology engineering, and mathematics (STEM) approach in the Kingdom of Saudi Arabia (build a suggested pro-posal) Researcher/ Maha Mohammed Shamroukh Al-Otaibi, Dr. Abdullah Awad Abdullah Al-Harbi 3. The impact of digital storytelling on motivation and achievement in teaching scientific concepts for Kindergarten children Researcher/ Najma Bint Nasser Al-Jabriya 4. Ethical Issues Related to Low Performance Among Saudi Students in the Trends in International Mathematics and Science Study (TIMSS) Noha Ali Almazroo